Transformasi Tanaman Tebu (cv. PSJT 94-41) dengan Gen Fitase Menggunakan Agrobacterium tumefaciens GV 2260 (pBinPI-IIEC) *] - , Susiyanti; G. A. Wattimena; M. Surahman; A. Purwito; D. A. Santosa (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
Phosphorus is a critical nutrient for the growth and development of sugarcane in the marginal land in Indonesia. P stored in plant  as phytic acid (myo-inositolhexakisphosphate).  The objective of the study was to increase activity  of phytases enzyme in sugarcanes (cv. PSJT 94-41) through phytase gene transformation. Detection of chimeric gene by PCR showed that the phytase gene was integrated into the genome of sugarcanes. Transformation caused some abnormality such as albino, discoloration, lack of chlorophyll in the particular spot of leaves.  Putative transgenic  plantlets expressed a  higher levels of phytase enzyme activity (38.1 %), whereas increase in P available in plant (19.5 %) and content of  chlorophyll (32.3 %).   Key words: Sugarcane, transformation, phytase,  Agrobacterium tumefaciens